Implantación de un sistema de contabilidad de costos para la microempresa Jolecc Sport de la ciudad de Latacunga para el primer semestre del año 2014 - Corrales Villegas, Soraya Elizabeth (2015)
The present investigation was raised given the need for the micro Jolecc Sport, as one of the main problems was to determine production costs in the development of sportswear and consequently determine the retail price, likewise determine its usefulness in a set period. For this reason we decided to implement a cost accounting system for production orders. In this research we use the following methods: deductive, analytical – synthetic method; the statistical method allowed to identify the needs that exist in the micro enterprise. The techniques to be used were the observation by itself which helped to verify the physical conditions of the microenterprises for the production of sportswear, customer service and sales….